2022
DOI: 10.3389/ffunb.2022.863198
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of Nematophagous Fungi in Determining the Activity of Plant Parasitic Nematodes and Their Prospective Role in Sustainable Agriculture

Abstract: In this review, we supply a framework for the importance of nematophagous fungi (nematophagous fungi [NF]) and their role in agricultural ecosystems. We characterize the taxonomy, diversity, ecology, and type of NF, depending on their interaction with plant-parasitic nematodes (PPNs). We described potential mechanisms of NF in the control of PPNs, the efficiency and methods of utilization, and the use of nematicides in sustainable agriculture. We explain the utilization of NF in nanotechnology as a new approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 83 publications
0
6
0
1
Order By: Relevance
“…Various studies carried out by several investigators like Goettel et al [ 18 ] and Al-Ani et al [ 19 ] revealed that Lecanicillium spp. has higher levels of egg parasitism than many other fungal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies carried out by several investigators like Goettel et al [ 18 ] and Al-Ani et al [ 19 ] revealed that Lecanicillium spp. has higher levels of egg parasitism than many other fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…has higher levels of egg parasitism than many other fungal species. The ovicidal potentiality may be referred to that conidia and hypha of nematophagous fungal taxa can easily penetrate the eggs and kill the juveniles [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF can be used in agriculture through the massive production of infective spores or through formulations that improve growth, viability, and efficacy [ 45 ]. They use several mechanisms of recognition, signaling, differentiation, and penetration of the cuticle or egg shell of nematodes through mechanical and enzymatic actions [ 46 ].…”
Section: Potential Of Nf In P Solubilizationmentioning
confidence: 99%
“…Microbes developed a wide array of strategies to target both motile and sedentary PPNs life stages. Through specialized structures, such as constricting rings, three-dimensional hyphae networks, and adhesive spores, for example, predatory fungi can trap nematodes and prevent them from escaping [ 21 , 22 ] ( Figure 1 ). Opportunistic saprotrophic fungi attack nonmotile stages, like eggs, cysts, and Meloidogyne females [ 23 ].…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%